An energy-efficient uwb transmitter with wireless injection locking for rf energy-harvesting sensors - Kim, Jun Tae; Heo, Bo Ram; Kwon, Ickjin (Sensors, 2021)
An ultralow-power ultrawideband (UWB) transmitter with an energy-efficient injection-locked radio frequency (RF) clock harvester that generates a carrier from an RF signal is proposed for RF energy-harvesting Internet-of-Things (IoT) sensor applications. The energy-efficient RF clock harvester based on the injection-locked ring oscillator (ILRO) is proposed to achieve optimal locking range and minimum input sensitivity to obtain an injection-locked 450 MHz clock in ultralow-power operation. A current-starved inverter-based delay stage is adopted that allows delay adjustment by bias voltage to minimize dynamic current consumption while maintaining a constant delay regardless of changes in process, supply voltage, and temperature (PVT). To minimize static current consumption, a UWB transmitter based on a digital-based UWB pulse generator and a pulse-driven switching drive amplifier is proposed. The proposed injection-locked RF clock harvester achieves the best RF input sensitivity of −34 dBm at a power consumption of 2.03 μW, enabling energy-efficient clock harvesting from low RF input power. In ultralow-power operation, a 23.8% locking range is achieved at the RF injection power of –15 dBm to cope with frequency changes due to PVT variations. The proposed UWB transmitter with RF clock harvester achieves the lowest energy consumption per pulse with an average power consumption of 97.03 μW and an energy consumption of 19.41 pJ/pulse, enabling operation with the energy available in RF energy-harvesting applications.
Keywords: Current-starved inverters; Dynamic current consumption; Injection-locked ring oscillators; Internet of Things (IOT); Radio frequency clocks; RF energy harvesting; Static current consumption; UWB pulse generator; Energy-harvesting sensor; Pulse generator; RF clock generator; RF energy harvesting; Transmitter; Ultrawideband